HPLC methods for clinical pharmaceutical analysis : a user's guide - Mascher, Hermann (Wiley-VCH, 2012)
The author describes all steps of a routine pharmaceutical analysis in an intuitive fashion and explains how to develop robust and efficient methods for any clinical compound. A reference appendix contains tried and tested methods for 100 freqently encountered pharmaceuticals.